Packet Tracing and Analysis of Network Cameras with Wireshark - Das, Resul; Tuna, Gurkan (Ieee, 2017)
Although people think that their identity is not revealed on the internet, the confidentiality and protection of personal information on unreliable networks such as the internet is an important question. In this study, a sample application on network packet tracing and analysis of network cameras with Wireshark program is realized to show how partial access to personal information and location information is obtained. As it is shown, network packets coming from/sent to IP cameras can be traced and analysed with Wireshark program. Moreover, it is shown that the location information can easily be obtained. This confirms that personal information can be captured and used for illegal purposes if the data is transferred over unreliable networks.
5th International Symposium on Digital Forensic and Security (ISDFS) -- APR 26-28, 2017 -- Tirgu Mures, ROMANIA
Keywords: Location Detection; Wireshark; OSI Reference Model Layers; Network Based Chat Systems